Low Molecular Weight Polyphenols in Cork of Quercus suber - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida; González Adrados, José Ramón (Journal of Agricultural and Food Chemistry, 1997)
Low molecular weight polyphenols were studied by HPLC in samples of cork from different trees of Spanish Quercus suber and at different industrial processing stages. Gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferylic, and sinapic aldehydes, and aesculetin and scopoletin were identified and quantified. Ellagic acid was the main component in all of the samples, followed by the rest of the phenolic acids, which had very much lower concentrations. Four components, caffeic, ferulic, and protocatechuic acids and vanillin, were selected as those that provided the greatest differences among the trees studied. In relation to the four industrial processing stages considered, marked differences were observed between the first two stages, stripping and first rest, and the stages after boiling. In this case, the discriminant variables were coniferaldehyde, sinapaldehyde, and ellagic acid. Keywords: Quercus suber; cork; polyphenols; phenolic acids and aldehydes; coumarins; high-performance liquid chromatography
doi: 10.1021/jf960486wdoi: 10.1021/jf960486wThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; coumarins; high- performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber

Low Molecular Weight Polyphenols in Cork of Quercus suber - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida; González Adrados, José Ramón (Journal of Agricultural and Food Chemistry, 1997)
Low molecular weight polyphenols were studied by HPLC in samples of cork from different trees of Spanish Quercus suber and at different industrial processing stages. Gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferylic, and sinapic aldehydes, and aesculetin and scopoletin were identified and quantified. Ellagic acid was the main component in all of the samples, followed by the rest of the phenolic acids, which had very much lower concentrations. Four components, caffeic, ferulic, and protocatechuic acids and vanillin, were selected as those that provided the greatest differences among the trees studied. In relation to the four industrial processing stages considered, marked differences were observed between the first two stages, stripping and first rest, and the stages after boiling. In this case, the discriminant variables were coniferaldehyde, sinapaldehyde, and ellagic acid. Keywords: Quercus suber; cork; polyphenols; phenolic acids and aldehydes; coumarins; high-performance liquid chromatography
doi: 10.1021/jf960486w
Keywords: Cork; coumarins; high- performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber

FACTORES QUE DETERMINAN LA CALIDAD DEL CORCHO - González Adrados, José Ramón (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Cork quality, strongly related with economical profit 9f Quercus suber stands, is today determined by the visual characteristics of corkwood planks, mainly porosity and thickness. Variance in those'parameters is imputed to ecologic?l, selvicultural and genetic factors. Relationship between environmental factors and cork qua lit y is studied in this work. Data from two samples obteined in Extremadura and Catalonia show that this dependence is significati ve.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Cork; Cork quality; Quercus suber stands

FACTORES QUE DETERMINAN LA CALIDAD DEL CORCHO - González Adrados, José Ramón (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Cork quality, strongly related with economical profit 9f Quercus suber stands, is today determined by the visual characteristics of corkwood planks, mainly porosity and thickness. Variance in those'parameters is imputed to ecologic?l, selvicultural and genetic factors. Relationship between environmental factors and cork qua lit y is studied in this work. Data from two samples obteined in Extremadura and Catalonia show that this dependence is significati ve.
Keywords: Cork; Cork quality; Quercus suber stands